Energy Conditions with Interacting Field in f(R) Gravity - Vasudeo Patil; Jeevan Pawde; Rahul Mapari; Pravin Bolke (East European Journal of Physics, 2023)
In the context of current scenario, it is crucial to look beyond Einstein’s theory, which opens the door to certain modified theories of gravity. So, present study is devoted to investigate the various energy conditions, particularly, strong energy condition (SEC), weak energy condition (WEC), null energy condition (NEC) and dominant energy condition (DEC) corresponding to different functional forms of f(R) gravity. We have studied for flat, isotropic and homogeneous FLRW cosmological model filled with interacting field i.e., perfect fluid is coupled with mass less scalar field for different models of modified f(R) gravity in which R is the Ricci scalar. We have observed, the accelerated expansion of the Universe which exact match with recent observational evidences.